RELATED TEACHING OF PHONETICS AND PHONOLOGY IS THE LEADING PRINCIPLE OF ORAL AND WRITTEN SPEECH SKILLS ACQUISITION - X. Gulomova (Galaxy International Interdisciplinary Research Journal, 2022)
The article notes that learning based on the relationship of phonetics with phonology, spelling and spelling is the leading principle for students to master the skills of oral and written speech.